Artificial Intelligence in accounting / Akma Hidayu Dol @ Abdul Wahid and Rafizan Abdul Razak - Dol @ Abdul Wahid, Akma Hidayu; Abdul Razak, Rafizan (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In the rapidly evolving landscape of the modern business world, the integration of artificial intelligence (AI) into the field of accounting has become a subject of increasing interest and importance. The development of AI-based technologies has transformed the accounting profession, presenting both opportunities and challenges for professionals in this domain. One of the primary advantages of incorporating AI into accounting is the potential for improved efficiency in various tasks, such as data analysis, financial reporting, and auditing (Gatea, 2024). AI is transforming the accounting field by automating tasks, providing insights, and enhancing decision-making. For instance, AI can automatically extract data from invoices, receipts, and other documents, thus reducing manual effort. Furthermore, AI algorithms can reconcile transactions and identify discrepancies. As a result, AI can generate standard financial reports in a much faster way than humans. AI helps accountants save time by handling daily tasks like entering data, matching transactions, and creating reports. This lets them focus on more important work that needs human thinking and skill (Anin Dyah Luthfiani, 2024). One example of accounting software that incorporates AI-driven features to enhance financial accounting and management is QNE AI Cloud Accounting. QNE AI Cloud Accounting is the newest product from QNE Software, designed for small and medium businesses and startups. It offers an easy-to-use and flexible accounting solution that can keep up with the fast-changing business world. Interestingly, the software introduces Quick Scan, a revolutionary feature that streamlines paperwork, reducing errors and saving time. The Optical Character Recognition Module (OCR) lets users scan printed or handwritten text from documents or images. It automatically changes the scanned text into digital text and saves it as a transaction record.